Evaluating parameters affecting non-participants supporting behavior in community-based tourism: a case of Banghuris Homestay - Meimand, Sajad Ebrahimi (2012)
Problems caused by non-participants in tourism activities in a host community and also community perceptions and participations have been attracted the attention of many tourism researchers over the past decades. In every community there are a number of residents who are not participating in tourism activities due to many unknown reasons and don?t consider tangible benefits of tourism. Non-participants in tourism activities may cause different problems in tourism development process, thus understanding their behavior toward tourism development seems crucial for a better planning. In this sense, this study tried to evaluate the supporting behavior of non-participants in Banghuris homestay, Malaysia. Currently, there are several models which tried to investigate factors influencing residents? supports for tourism development, but most of them didn?t consider attitudes of non-participants. In addition, this study modified Gursoy, Jurowski and Uysal model to a useful model for evaluation of non-participants supporting behavior toward tourism development. 30 non-participants interviewed during the data collection phase by in-depth interview sessions. The results revealed that there are eight main influencing parameters on Banghuris homestay non-participants; Relation with current participants, Time Limitations, Capital limitations, Livelihood status, Religious sensitivities, Envious sensitivities, Tourism Knowledge and Communication Barriers